IMPLEMENTATION OF PLAY ENVIRONMENT ARRANGEMENTS TO SUPPORT QUALITY LEARNING PROCESSES - Dwi Asti; Elida HS; Eli Maryani; Novita; Irma Yuliantina; Harlina (Universitas Panca Sakti Bekasi, 2024)
A quality learning process could be encouraged by a good play environment. The preparation for early childhood education program includes arranging various play activities with resources and instruments that can support children's learning from the surrounding environment and help them acquire the knowledge and abilities needed to achieve learning objectives. Education for early childhood is very dependent on how the play environment is organized. The environment can be likened as child's learning intermediary. The purpose of this research is to find out the implementation of play environment organization to support qualified learning process. These used qualitative method. The qualitative research is a research which analyze, describe moments, social activity, phenomenon, belief, manner as well as individual and group thoughts. The research result showed that after play environment has been organized, thus influence the achievement of learning objectives, children learning motivation, children centre learning environment, supporting children curiosity to explore their idea and interest. This research was held at 50 play groups, resulted interest and learning passion shifting on children, from small number of enthusiasm into almost all children enthusiast to learn and actively participate in the process. Teacher motivation also increases to provide interesting and fun activities for children. Teaching pattern shifted from one activity focus into various activities or option by utilizing tools and materials around them. This research showed the play environment organization encourages the quality learning process.